Axiomatization of divisor methods and weakly degressive proportionality - Dniestrzański, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The paper analyzes the differences between weakly degressive proportionality and proportional allocations represented by divisor methods. The analysis is accomplished by the axiomatization of divisor methods in line with Balinski and Young
Didactics of Mathematics, 2017, Nr 14 (18), s. 19-26
Keywords: degressive proportionality; fair division; axiomatization of divisor methods